Program Halakah Jurnal Ilmiah (HAJI): Mentoring Peningkatan Pemahaman dan Keterampilan Penulisan Jurnal Ilmiah - Khaerul Aqbar; Awal Rifai; Dewi Indriani; Jamaluddin, Jamaluddin; Muhammad, Muhammad; Nabilah Al Azizah; Azwar, Azwar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
Writing high-quality academic articles is a challenge for many academics at developing higher education institutions, including at Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar. These challenges include a lack of understanding regarding proper writing formats, appropriate research methodologies, publication ethics standards, and language barriers, particularly in writing scholarly work in English. This Community Service Program (PkM), in the form of the Scientific Journal Halakah Program (HAJI), aims to enhance the understanding and skills of lecturers in writing scientific journal articles through intensive guidance and systematic mentoring, especially for novice lecturers, in the process of producing high-quality academic articles. The methods used in this program include face-to-face lectures, discussions, and hands-on practice through several group/halakah sessions. This program successfully enhanced the understanding and skills of lecturers, particularly novice lecturers, in academic journal writing through intensive guidance and systematic mentoring. Evaluation results indicate that the program was both relevant and effective, as participants demonstrated improved comprehension of journal manuscript structure, research methodologies, the review process, and the use of reference management tools. Additionally, the program boosted participants' confidence in scientific publication and provided new insights into publication ethics. The program’s success has positively impacted the quality of lecturers’ articles, enhanced the institution’s reputation, and fostered a writing culture that supports research quality and innovation at STIBA Makassar.